Perceived Social Support and Psychological Well-Being in Patients with Chronic Diseases - Yıldırım, Dilek; Akman, Özlem; Dokumacı, Duygu; Dokumacı, Duygu (Balıkesir Üniversitesi, 2023)
Objective: In the literature reported that perceived social support may have a positive impact on psychological well-being of patients with chronic diseases. However, a brief review of the literature also shows that the number of studies on the relationship between perceived social support and psychological well-being in patients with chronic diseases is limited. This study aims to determine the relationship between perceived social support and psychological well-being in patients with chronic diseases. Materials and Methods: This descriptive and correlational study was conducted on 203 inpatients with at least one chronic disease, who received treatment at a community health center between November 2020 and May 2021 in İstanbul. Results: Psychological well-being of the participants was positively correlated with perceived social support. Duration of chronic disease and age of participants were negatively correlated with perceived social support and psychological well-being. Simple linear regression model that analyzed the effects of perceived social support on psychological well-being of the participants was statistically significant (p<0.001) and showed that perceived social support explained about 18% of the change in the psychological well-being of participants with chronic diseases (straight, R2 = 0.175). The determination coefficient of the model was 0.161. A positive correlation was determined between MSPSS and FS scores. Conclusions: The findings implied that perceived social supported improved psychological well-being of patients with chronic diseases. Therefore, health professionals, primarily the nurses, may evaluate the levels of perceived social support and psychological well-being of patients with chronic diseases and incorporate spiritual care interventions and social support systems into nursing care plans.

Amaç: Bu çalışmanın amacı kronik hastalığı olan hastalarda algılanan sosyal destek ile psikolojik iyi oluş arasındaki ilişkiyi belirlemektir. Gereç ve Yöntem: Tanımlayıcı ve korelasyonel tipteki bu çalışma, Kasım 2020-Mayıs 2021 tarihleri arasında İstanbul’da bulunan bir toplum sağlığı merkezinde en az bir kronik hastalığı olan 203 hasta üzerinde yürütüldü. Bulgular: Katılımcıların psikolojik iyi oluşluk durumları ile algılanan sosyal destek düzeyleri arasında pozitif yönlü anlamlı bir ilişki vardı. Kronik hastalık süresi ve katılımcıların yaşı, algılanan sosyal destek ve psikolojik iyi oluşluk ile negatif ilişkiliydi. Algılanan sosyal desteğin katılımcıların psikolojik iyi oluşluk üzerindeki etkilerini analiz eden basit doğrusal regresyon modeli istatistiksel olarak anlamlıydı (p<0.001) ve algılanan sosyal desteğin kronik hastalığı olan katılımcıların psikolojik iyi olma halindeki değişimin yaklaşık %18’ini açıkladığını gösterdi (straight, R2=0.175). Modelin belirleme katsayısı 0.161'dir. MSPSS ve FS puanları arasında istatistiksel olarak anlamlı pozitif yönlü bir ilişki belirlendi. Sonuç: Bu çalışmanın sonuçları algılanan sosyal desteğin kronik hastalığı olan hastaların psikolojik iyi oluşluğu iyileştirdiğini göstermektedir. Bu nedenle, başta hemşireler olmak üzere sağlık profesyonelleri, kronik hastalığı olan hastaların algılanan sosyal destek ve psikolojik iyi oluşluk düzeylerini değerlendirebilir ve hemşirelik bakım planlarına manevi bakım müdahalelerini ve sosyal destek sistemlerini dahil edebilirler.
Kronik Hastalığı Olan Bireylerin Algıladıkları Sosyal Destek ve Psikolojik İyi Oluş Düzeylerinin Belirlenmesi
Keywords: Chronic Disease; Social Support; Psychology; Health; Care; Nursing Care; Kronik Hastalık; Sosyal Destek; Psikoloji; Sağlık; Bakım; Hemşirelik Bakımı